Mastering plot twists : how to use suspense, targeted storytelling strategies, and structure to captivate your readers - Cleland, Jane K (Writer's Digest Books, 2018)
"The key to keeping readers on the edge of their seats is filling your stories--from memoirs to thrillers and stage plays to screenplays--with unexpected twists and turns. By integrating Plot *T*wists, Plot *R*eversals, and Moments of Heightened *D*anger (TRDs) at crucial points, you can captivate your readers with I-can't-wait-to-see-what-happens-next intrigue. The quicker pace and focused action that come from strategically placed twists form the core of the nuanced, multifaceted books that sell--and that help you find a devoted readership. In Mastering Plot Twists, Agatha Award-winning author Jane K. Cleland goes beyond telling writers what to do; she shows you how to do it. Within these pages, you'll find: a proven, five-step process for using TRDs, with detailed examples from best-selling books; a deep dive into plotting, structure, pacing, subplots, and more to help you develop surprising yet inevitable twists; "Jane's Plotting Roadmap" and worksheets--essential tools for planning your plot. Building on the award-winning instruction provided in Mastering Suspense, Structure, & Plot, Cleland's newest guide will help you write effective and credible twists, creating the kind of stories that will keep your readers up long into the night."--Back cover.